Interactive Multimedia Development Based on TPACK IPAS Subjects for Grade IV Elementary School Students - Rini Nelwideri; Rayendra; Fetri Yeni J; Ramalis Hakim (Postgraduate, University of Mataram, 2025)
This research aimed to develop an interactive multimedia based on TPACK (Technological Pedagogical Content Knowledge) for the IPAS (Science and Social Studies) subject in Grade IV at SDN 22 Cacang Randah, Kabupaten Agam. The study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) for the development process. The results showed that the developed multimedia was valid, practical, and effective for use in the classroom. The validation process, carried out by education experts, indicated that the multimedia met the learning goals and was well-designed. The practical implementation of the multimedia, as assessed by both teachers and students, confirmed its ease of use and accessibility. Additionally, effectiveness tests conducted through pretests and posttests revealed a significant improvement in students' understanding of the material, with an average N-gain score of 85.90%, categorized as high. The multimedia supported the development of critical thinking and enhanced student engagement, aligning with the principles of Kurikulum Merdeka. In conclusion, the interactive multimedia based on TPACK is a valid, practical, and effective tool for enhancing the learning experience in elementary school education. Further studies with larger sample sizes and broader topics are recommended to explore its long-term effectiveness.